A highly nonlinear transparent glass-ceramic
By performing microcrystallization heat treatment on the Ge-S chalcogenide glass material mixed with CsCl, a transparent glass-ceramic containing β-GeS2 crystals or a mixed crystal of β-GeS2 and α-GeS2 coexisting is formed, which solves the problem that is difficult to provide in the existing technology. The problems of good thermal stability, high transmittance and non-linear absorption characteristics enable an efficient preparation process and excellent performance.
Patent Information
- Application Number
- CN202211560579.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-07
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2042-12-07
AI Technical Summary
The prior art is difficult to provide a highly nonlinear transparent microcrystalline glass with good thermal stability, high transmittance, good mechanical properties, excellent nonlinear absorption characteristics and easy to process.
By mixing the CSCL GE-S sulfur glass material for microcrystalline thermal treatment, a transparent microcrystalline glass containing β-GES2 crystals or β-GES2 and α-GES2 coexist. The treatment temperature is between 370 and 400 ° C. The specific steps include ingredients, vacuum, high temperature melting, quenching, annealing and microcrystalline thermal treatment.
The preparation of highly nonlinear transparent glass-ceramics has been achieved. It has excellent nonlinear absorption characteristics, good mechanical properties and high transmittance. It is suitable for the field of optical limiting device manufacturing, and the preparation process can save energy.
Smart Images

Figure CN116002979B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of highly nonlinear optical glass, in particular to highly nonlinear transparent microcrystalline glass. Background Art
[0002] As integrated circuit technology enters the "post-Moore era", the era of blindly pursuing the reduction of process technology to promote the development of integrated circuits is gone forever due to the quantum effect brought about by the reduction of integrated circuit process. Since photons have no charge, there is almost no interference between each other, so there will be no problems with electrons during transmission, making photon integration technology increasingly concerned by the scientific and industrial communities in the development of the future information society. The development and preparation of new highly nonlinear optical materials as the basis of photon integration technology in a low-energy way is a crucial link in the development of optoelectronic information technology. Among the many glass materials, chalcogenide glass has established its important position in infrared photon integrated devices and technologies with its advantages such as high linear refractive index, ultra-short nonlinear response and ultra-wide infrared transmission range.
[0003] Sulfur-based glass-ceramics, as a new type of glass-ceramic material, refers to a composite material in which at least one crystalline phase is embedded in a sulfide glass matrix. Based on the advantages of sulfide glass, sulfide glass-ceramics have the advantages of more excellent mechanical strength, thermal stability and optical nonlinear performance. As a kind of nonlinear characteristics, the third-order optical nonlinear characteristics often become the focus of people's attention when considering the application and commercial value of materials. For example, high nonlinear absorption is an important factor that must be considered when developing materials to protect human eyes and optical sensing equipment from laser damage. Embedding nanocrystals in the sulfide glass matrix and utilizing their size restriction effect to improve nonlinear absorption is a new approach at present and in the future. However, the selection of materials and nucleating agents has become the key that must be considered to balance transmittance and nonlinear absorption. Based on this, the present invention proposes a highly nonlinear transparent glass-ceramics to provide guidance for the design and optimization of the performance of new materials. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a highly nonlinear transparent microcrystalline glass with good thermal stability, high transmittance, good mechanical properties, excellent nonlinear absorption characteristics and easy mechanical processing in view of the shortcomings of the prior art.
[0005] The technical solution adopted by the present invention to solve the above technical problems is: a highly nonlinear transparent microcrystalline glass, the composition formula of which is Ge 30 S 50 (CsCl) 20 The transparent glass-ceramic contains microcrystals with CsCl as nucleating agent, wherein the microcrystals are β-GeS2 Crystal or β-GeS 2 Crystal and α-GeS 2 Mixed crystals where crystals coexist.
[0006] Preferably, the temperature of the microcrystallization heat treatment is 370-400°C.
[0007] In a preferred embodiment, the temperature of the microcrystallization heat treatment is 370-380°C, and the microcrystal is β-GeS 2 Specifically, the β-GeS 2 The crystal is composed of ethane-like structure [S 3 Ge-GeS 3 ], discrete [GeS 4 ]tetrahedron, corner-sharing and edge-sharing [GeS 4 ]Tetrahedron composition.
[0008] In another preferred embodiment, the temperature of the microcrystallization heat treatment is 390°C, and the microcrystal is β-GeS 2 Crystal and α-GeS 2 The crystal size of the granular mixed crystals is 25-35nm. The maximum nonlinear absorption coefficient of the transparent microcrystalline glass obtained by microcrystallization heat treatment at 390℃ is 23.48cm / GW, which is 19 times that of the matrix glass. This shows that the transparent microcrystalline glass obtained by microcrystallization heat treatment at 390℃ has excellent nonlinear absorption characteristics and is suitable for use in the field of optical limiting device manufacturing.
[0009] In the third preferred embodiment, the temperature of the microcrystallization heat treatment is 400°C, and the microcrystal is β-GeS 2 Crystal and α-GeS 2 Layered mixed crystals with coexistence of crystals.
[0010] Specifically, the method for preparing the highly nonlinear transparent glass-ceramics comprises the following steps:
[0011] (1) Ingredients and vacuuming: Calculate the required amount of each element according to the glass composition, weigh the high-purity germanium, sulfur, and cesium chloride raw materials, and control the error within ±0.001g. Then slowly pour the raw materials into a dry and clean quartz tube and vacuum the quartz tube to 10 -4 ~10 -7 Pa, encapsulate the raw materials in a quartz tube;
[0012] (2) High-temperature melting and quenching: The sealed quartz tube containing the raw materials is placed in a rocking furnace for high-temperature melting at a melting temperature of 800°C for a melting time of 3 to 7 hours. After the melting is completed, the quartz tube is taken out of the rocking furnace and then immersed in a NaOH aqueous solution to quench the encapsulated melt. After the wall is observed to be detached, it is immediately taken out to obtain a semi-finished chalcogenide glass material doped with CsCl in the quartz tube;
[0013] (3) Annealing and cooling: The semi-finished chalcogenide glass material doped with CsCl is annealed together with the quartz tube, the annealing temperature is 300-320°C, the annealing time is 3 hours, and after the annealing is completed, the temperature is cooled to room temperature at a cooling rate of 9-10°C / h, and then the quartz tube is taken out of the annealing furnace and opened to obtain the finished chalcogenide glass material doped with CsCl;
[0014] (4) The finished chalcogenide glass material doped with CsCl is subjected to microcrystallization heat treatment at a temperature range of 370-400°C for 5 hours to obtain a highly nonlinear transparent microcrystalline glass, the composition of which is Ge 30 S 50 (CsCl) 20 .
[0015] Compared with the preparation method of traditional chalcogenide glass, the preparation, annealing and heat treatment temperature of the preparation method of the present invention is lower and the time is shorter. Therefore, the energy required to prepare the transparent microcrystalline glass of the present invention can save more energy consumption than traditional chalcogenide glass.
[0016] Compared with the prior art, the present invention has the following advantages:
[0017] The highly nonlinear transparent microcrystalline glass of the present invention is obtained by subjecting a Ge-S chalcogenide glass material doped with CsCl to microcrystallization heat treatment. The transparent microcrystalline glass contains microcrystals with CsCl as a nucleating agent, wherein the microcrystals are β-GeS 2 Crystal or β-GeS 2 Crystal and α-GeS 2 Mixed crystals with coexisting crystals. The type of microcrystals contained is related to the microcrystallization heat treatment temperature. As the microcrystallization heat treatment temperature changes, corresponding crystals are generated inside the glass, and the corresponding microstructure also changes: from no crystals to [S 3 Ge-GeS 3 ], discrete [GeS 4 ]tetrahedron, corner-sharing and edge-sharing [GeS 4 ] Tetrahedral β-GeS 2 Crystal, then β-GeS 2 The crystal is highly aggregated and transformed into β-GeS 2 Crystal and α-GeS 2The granular mixed crystals coexisted and eventually transformed into β-GeS 2 Crystal and α-GeS 2 Layered mixed crystals with coexisting crystals. Thanks to the changes in the glass microstructure, the transparent microcrystalline glass of the present invention has the advantages of good chemical stability and thermal stability, high transmittance, high hardness, excellent and adjustable nonlinear absorption characteristics, easy fiberization and film formation, and convenient mechanical processing. The formation of the internal crystal structure of the transparent microcrystalline glass of the present invention does not affect its optical and mechanical properties. Tests have shown that its transmittance is between 67 and 85%, the maximum nonlinear absorption coefficient is 23.48 cm / GW, and the Vickers hardness can reach up to 294 kg / mm 2 It is an excellent non-resonant nonlinear optical material for preparing optical limiting devices and has immeasurable application value in the future optoelectronic field. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 A schematic diagram of the structure of the Z scanning experimental device used in the present invention;
[0019] Figure 2 It is the Z scanning test result curve of the glass samples of the blank group, comparative example 1, embodiment 1, and embodiment 3;
[0020] Figure 3 The transmission spectra of the glass samples of the blank group, comparative examples 1 to 2 and examples 1 to 4 in the visible light band (0.4400 to 12.5 μm);
[0021] Figure 4 XRD patterns of the glass samples of the blank group, comparative examples 1 to 2, and examples 1 to 4;
[0022] Figure 5 is the transmission electron microscope spectrum of the glass sample of Example 3;
[0023] Figure 6 This is a scanning electron microscope image of the glass sample of Example 4. DETAILED DESCRIPTION
[0024] The present invention is further described in detail below with reference to the accompanying drawings.
[0025] The composition formula of the highly nonlinear transparent glass-ceramics of Examples 1 to 4 is Ge 30 S 50 (CsCl) 20 , which is obtained by subjecting a Ge-S chalcogenide glass material doped with CsCl to microcrystallization heat treatment. The preparation method of the highly nonlinear transparent microcrystalline glass of Examples 1 to 4 specifically comprises the following steps:
[0026] (1) Ingredients and vacuuming: According to the glass composition, calculate the required amount of each element, use an electronic balance to weigh high-purity germanium (99.999%, 5N), sulfur (5N), and cesium chloride raw materials (4N), and control the error within ±0.001g. Then mix the raw materials evenly and slowly pour them into a dry and clean quartz tube. Vacuum the quartz tube to 10 -7 Pa, encapsulate the raw materials in a quartz tube;
[0027] (2) High-temperature melting and quenching: The sealed quartz tube containing the raw materials is placed in a rocking furnace for high-temperature melting, and the heating rate is strictly controlled to make the temperature rise in steps to prevent the pressure in the tube from rising sharply and causing the tube to burst. The melting temperature is 800°C and the melting time is 5 hours. After the melting is completed, the quartz tube is taken out of the rocking furnace and then immersed in a NaOH aqueous solution to quench the encapsulated melt. After the wall is observed to be detached, it is immediately taken out to obtain a semi-finished chalcogenide glass material doped with CsCl in the quartz tube;
[0028] (3) Annealing and cooling: the semi-finished chalcogenide glass material doped with CsCl is annealed together with the quartz tube, the annealing temperature is 310°C, the annealing time is 3 h, and after the annealing is completed, the temperature is lowered to room temperature at a cooling rate of 10°C / h, and then the quartz tube is taken out of the annealing furnace and opened to obtain the finished chalcogenide glass material doped with CsCl;
[0029] (4) The finished chalcogenide glass material doped with CsCl is subjected to microcrystallization heat treatment at a temperature range of 370 to 400°C for 5 hours to obtain a highly nonlinear transparent microcrystalline glass, the composition of which is Ge 30 S 50 (CsCl) 20 .
[0030] The preparation methods of highly nonlinear transparent microcrystalline glass in Examples 1 to 4 differ only in the temperature of microcrystallization heat treatment, and the other steps and parameters are the same. Specifically, the temperatures of microcrystallization heat treatment in Examples 1 to 4 are 370°C, 380°C, 390°C and 400°C, respectively.
[0031] For comparison, a blank group and glasses of comparative examples 1 and 2 were selected. The difference from Example 1 is that the glass of the blank group is matrix glass and has not been subjected to the microcrystallization heat treatment of step (4); the temperature of microcrystallization heat treatment of the glass of comparative example 1 is 350°C; the temperature of microcrystallization heat treatment of the glass of comparative example 2 is 360°C.
[0032] Here, the following Figure 2 to Figure 4In the figure, GSC-0, GSC-1, GSC-2, GSC-3, GSC-4, GSC-5, and GSC-6 represent the glass samples of the blank group, comparative example 1, comparative example 2, example 1, example 2, example 3, and example 4, respectively.
[0033] The physical and optical parameters of the glass samples of the blank group, comparative examples 1 to 2 and examples 1 to 4 are shown in Table 1, where H v represents Vickers hardness, λ s represents the short-wave absorption cutoff edge, E opg It can be seen from Table 1 that the hardness values of Examples 1 to 4 and Comparative Examples 1 to 2 are all higher than those of the blank group, which indicates that the crystals precipitated in the glass matrix by microcrystallization heat treatment can effectively improve the mechanical strength of the glass, and as the crystals are further precipitated, the overall structure of the glass micro-network is improved, thereby improving its mechanical properties.
[0034] Table 1: Physical and optical parameters of glass samples
[0035]
[0036] For the glass samples of the blank group, comparative example 1, example 1, and example 3, the nonlinear absorption coefficients at wavelengths of 750 nm, 800 nm, 850 nm, and 900 nm were tested by open-hole Z scanning experiments, respectively. The experimental apparatus is as follows: Figure 1 As shown. In the experiment, a wavelength-tunable titanium sapphire femtosecond laser (Chameleon Ultra II, USA) was used as the laser source. Its wavelength adjustment range is 680-1080nm, the repetition frequency is 80MHz, the pulse width is 140fs, and the power stability is ±3%. After the pump light passes through a high-reflection mirror, it is divided into two beams by a semi-transparent and semi-reflective beam splitter (the reflectivity and transmittance are 45% and 55% respectively). One beam of light is detected by power detector 1 as the reference light source of the incident power, and the other beam of light is focused by a double convex mirror and irradiated onto the glass sample. The transmitted beam is received by optical power detector 2. The power signals received by power detector 1 and power detector 2 are respectively input into the EM2000 dual-channel power meter of Coherent. During the experiment, the position of the sample is adjusted by a stepper motor controller, and the readings of the power meter are recorded, so as to obtain a set of Z-scan data corresponding to the sample position and the transmitted power. It should be pointed out that the above tests were all carried out at room temperature.
[0037] The Z scanning test result curves of the glass samples of the blank group, comparative example 1, example 1 and example 3 are shown in FIG. Figure 2 .from Figure 2It can be seen that at any wavelength, the transmitted power at the focus of the sample that has undergone microcrystallization heat treatment shows a gradually decreasing trend compared to the blank group, indicating that microcrystallization heat treatment can gradually increase the nonlinear absorption coefficient.
[0038] Table 2 shows the nonlinear absorption coefficient β of the glass samples at different wavelengths obtained through fitting calculation. The nonlinear absorption coefficient β of the blank group sample at a wavelength of 900nm is 1.29cm / GW, which is the minimum value. The maximum nonlinear absorption coefficient is obtained in Example 3 at a wavelength of 750nm, and its nonlinear absorption coefficient β is 23.48cm / GW.
[0039] As for the glass sample of Example 3, due to the crystals embedded in the glass matrix, the glass generates a new valence state between the valence band and the conduction band, so that it can absorb photons with energy lower than the band gap, and then complete the transition behavior of electrons between the band gaps. Therefore, at a specific wavelength, the β value will increase with the increase of the heat treatment temperature, thereby improving the two-photon absorption. From the data in Table 2, it can be seen that due to the better resonance effect of the photon energy of 750nm wavelength and the defect states in the microcrystalline glass sample at the focus, the nonlinear absorption is enhanced. Therefore, compared with other wavelengths, under the irradiation of 750nm laser wavelength, with the increase of the microcrystallization heat treatment temperature, the transmitted power of the sample at the focus is significantly reduced, and it has a better nonlinear absorption effect. At the same time, from an overall analysis, due to the quantum effect of the nanocrystals, that is, GeS and GeS confined in the glass matrix 2 The nanoparticles cause the valence and conduction bands to decompose into a series of discrete energy levels, making the nonlinear characteristics increase with the increase of crystallinity at the incident wavelength. Through the change and interaction of the electron quantum state in the light field, the intraband transition of the electrons in the glass matrix increases, resulting in changes in nonlinear absorption.
[0040] Table 2: Nonlinear absorption coefficients of glass samples
[0041]
[0042] Figure 3 The transmission spectra of the glass samples of the blank group, comparative examples 1 to 2, and examples 1 to 4 in the visible light band (0.4400 to 12.5 μm) are shown. Figure 3 It can be seen that in the wide range from near-infrared to mid-infrared, the prepared glass samples (matrix glass, microcrystalline glass) have good transparency. Figure 4 The XRD patterns of the glass samples of the blank group, comparative examples 1 to 2, and examples 1 to 4 are shown. As the temperature of the microcrystallization heat treatment changes, corresponding crystals ( Figure 4 This indicates that with the assistance of the nucleating agent CsCl, the crystallization properties of the glass are significantly improved. Figure 5 The transmission electron microscope (TEM) spectrum of the glass sample of Example 3 is shown. Figure 6 The scanning electron microscope (SEM) image of the glass sample of Example 4 is shown. Figures 4 to 6 It can be seen that the changes in the crystal structure inside the glass can be summarized as follows according to the temperature change:
[0043] (1) For the blank group, comparative example 1 and comparative example 2, simply Figure 4 From the XRD spectrum, it can be seen that the interior of the glass is uniform and no crystals appear;
[0044] (2) For Example 1, according to Figure 4 From the XRD spectrum, it can be seen that there are tiny crystal peaks, and the crystal structure is composed of ethane-like structures [S 3 Ge-GeS 3 ], discrete [GeS 4 ]tetrahedron, corner-sharing and edge-sharing [GeS 4 ] Tetrahedral β-GeS 2 Crystal, at this time, the crystal aggregation is small, so the crystal peak is not obvious;
[0045] (3) For Example 2, due to the increase in the microcrystallization heat treatment temperature, according to the Ostwald ripening theory, the crystals inside the glass further aggregate and the crystal size further increases. Figure 4 The XRD pattern shows that the crystal peak does not change but the intensity increases;
[0046] (4) For Example 3, the microcrystallization heat treatment temperature was further increased, which promoted the change of crystals in the glass. Figure 4 In the XRD graph, we can see that while the original crystal peak exists and grows, a new crystal peak appears. This indicates that a new crystal structure appears inside the crystal. After analysis, we know that the new crystal peak is a two-dimensional α-GeS 2 Crystal, at this time the microcrystal inside the material is β-GeS 2 Crystal and α-GeS 2 Granular mixed crystals with coexisting crystals;
[0047] (5) For Example 4, the microcrystallization heat treatment temperature reaches 400°C. Figure 4 The XRD spectrum of the glass shows that the internal structure has changed significantly, which is manifested in the appearance of more fine peaks. Figure 6 After SEM analysis, it can be confirmed that the microcrystals at this time are β-GeS 2 Crystal and α-GeS 2 Layered mixed crystals with coexistence of crystals.
[0048] For the glass sample of Example 3, Figure 5 The TEM image analysis shows that the size of each stage of the crystal in the glass is kept at about 30nm, and its structure is generally composed of three-dimensional β-GeS 2 The crystal structure is transformed into three-dimensional β-GeS 2 Crystal structure and two-dimensional α-GeS 2 The crystal structure of the coexistence of crystals. And because the scattering loss increases in the UV-vis-NIR region as the size of the precipitated crystals approaches the incident wavelength, the optical transmittance of the microcrystalline glass decreases, and its short-wave cutoff edge shows a slight tilt. The transmittance of the GSC sample is related to the refractive index mismatch between the grains and the glass matrix and decreases slightly as the crystal particles gradually increase.
Claims
1. A highly nonlinear transparent glass-ceramic, characterized in that: The composition formula of the transparent glass-ceramic is Ge 30 S 50 (CsCl) 20 It is obtained by microcrystallization heat treatment of CsCl-doped Ge-S chalcogenide glass material. The transparent microcrystal contains microcrystals with CsCl as a nucleating agent. The temperature of the microcrystallization heat treatment is 390°C. The microcrystals are granular mixed crystals in which β-GeS2 crystals and α-GeS2 crystals coexist, and the crystal size is 25 to 35 nm.
2. The highly nonlinear transparent glass-ceramics according to claim 1, characterized in that: The temperature of the microcrystallization heat treatment is 370-400°C.
3. The highly nonlinear transparent glass-ceramics according to claim 2, characterized in that: The temperature of the microcrystallization heat treatment is 370-380°C, and the microcrystals are β-GeS2 crystals.
4. The highly nonlinear transparent glass-ceramics according to claim 3, characterized in that: The β-GeS2 crystal is composed of [S3Ge-GeS3] of ethane-like structure, discrete [GeS4] tetrahedron, and [GeS4] tetrahedron sharing corners and edges.
5. The highly nonlinear transparent glass-ceramics according to claim 1, characterized in that: The temperature of the microcrystallization heat treatment is 400° C., and the microcrystals are layered mixed crystals in which β-GeS2 crystals and α-GeS2 crystals coexist.
6. The highly nonlinear transparent glass-ceramic according to claim 1, characterized in that: The preparation method of the transparent microcrystalline glass comprises the following steps: (1) Ingredients and vacuuming: Calculate the required amount of each element according to the glass composition, weigh the high-purity germanium, sulfur, and cesium chloride raw materials, and control the error within ±0.001g. Then slowly pour the raw materials into a dry and clean quartz tube and vacuum the quartz tube to 10 -4 ~10 -7 Pa, encapsulate the raw materials in a quartz tube; (2) High-temperature melting and quenching: The sealed quartz tube containing the raw materials is placed in a rocking furnace for high-temperature melting at a melting temperature of 800°C for a melting time of 3 to 7 hours. After the melting is completed, the quartz tube is taken out of the rocking furnace and then immersed in a NaOH aqueous solution to quench the encapsulated melt. After the wall is observed to be detached, it is immediately taken out to obtain a semi-finished chalcogenide glass material doped with CsCl in the quartz tube; (3) Annealing and cooling: The semi-finished chalcogenide glass material doped with CsCl is annealed together with the quartz tube, the annealing temperature is 300-320°C, the annealing time is 3 hours, and after the annealing is completed, the temperature is cooled to room temperature at a cooling rate of 9-10°C / h, and then the quartz tube is taken out of the annealing furnace and opened to obtain the finished chalcogenide glass material doped with CsCl; (4) The finished chalcogenide glass material doped with CsCl is subjected to microcrystallization heat treatment at a temperature range of 370-400°C for 5 hours to obtain a highly nonlinear transparent microcrystalline glass, the composition of which is Ge 30 S 50 (CsCl) 20 .